Guillain-Barre Syndrome Presenting with Acute Motor Sensory Neuropathy following a MRSA Infection: A Case Report - Priyanka, Thommanduru; Lekhanth, Alluru; Revanth, Alluru (Indian Journal of Pharmacy Practice)
A case report is presented of a 3-year-old boy who came with the complaints of weakness of lower limbs since 5 days and upper limbs since 3 days. On examination he had generalized hypotonia and areflexia. Power of the limbs was low with weak grip. Sensory and motor nerve conduction studies revealed acute motor axonal neuropathy involving both upper and lower limbs. Culture of blood and sputum revealed MRSA infection. Patient was managed with IV fluids and broad spectrum IV antibiotics. He was started on IvIg. The clinical manifestation of Guillain-Barre syndrome followed a combined MRSA infection. So this case report reveals an evolutionary significanceantecedent infection to the cause of Guillain-Barre syndrome.
Keywords: Acute motor axonal neuropathy; Guillain-Barre Syndrome; IvIg; MRSA infection; Neurological disorder